2015
DOI: 10.3389/fphar.2015.00222
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of HDL

Abstract: High-density lipoprotein (HDL) provides a pathway for the passage of lipid peroxides and lysophospholipids to the liver via hepatic scavenger receptors. Perhaps more importantly, HDL actually metabolizes lipid hydroperoxides preventing their accumulation on low-density lipoprotein (LDL), thus impeding its atherogenic structural modification. A number of candidates have been suggested to be responsible for HDL's antioxidant function, with paraoxonase-1 (PON1) perhaps the most prominent. Here we review the evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 52 publications
6
96
0
6
Order By: Relevance
“…This result was also confirmed in our study in isolated HDL lipoprotein fractions and suggested reduced antioxidant potential of HDL particles in renal disease . Given that free SH‐groups have the potential to neutralize oxidized phospholipids and cholesterol esters, decreased PON1 in serum, as well as in isolated HDL lipoprotein fractions may lead to oxidative damage of other lipoproteins, including HDL particles . In addition, increased uremic toxins could be an additional reason for decreased PON1 concentration in renal patients due to interference with the synthesis of PON1 itself .…”
Section: Pon1 and Diseases Connected With Atherosclerosis Developmentsupporting
confidence: 87%
“…This result was also confirmed in our study in isolated HDL lipoprotein fractions and suggested reduced antioxidant potential of HDL particles in renal disease . Given that free SH‐groups have the potential to neutralize oxidized phospholipids and cholesterol esters, decreased PON1 in serum, as well as in isolated HDL lipoprotein fractions may lead to oxidative damage of other lipoproteins, including HDL particles . In addition, increased uremic toxins could be an additional reason for decreased PON1 concentration in renal patients due to interference with the synthesis of PON1 itself .…”
Section: Pon1 and Diseases Connected With Atherosclerosis Developmentsupporting
confidence: 87%
“…38 The HDL-binding glycoprotein PON-1 is shown to be critical for the antioxidative capacity of HDL. 42 A previously published association of low PON-1 activity and poor longterm prognosis in patients with CHF was visible in our cohort in unadjusted Cox regression analysis but turned nonsignificant after adjustment for potential confounders including implementation of HOI in our multivariable model. 17 Although we saw a significant association between PON-1 activity and the measured antioxidative capacity in the unadjusted model, this relationship was no longer observed after multivariable adjustment.…”
Section: Discussionsupporting
confidence: 49%
“…HDL particles are composed of lipids and more than 100 different proteins and exert their protective functions by the collaboration of essential apolipoproteins and associated enzymes . The HDL‐binding glycoprotein PON‐1 is shown to be critical for the antioxidative capacity of HDL . A previously published association of low PON‐1 activity and poor long‐term prognosis in patients with CHF was visible in our cohort in unadjusted Cox regression analysis but turned nonsignificant after adjustment for potential confounders including implementation of HOI in our multivariable model .…”
Section: Discussionmentioning
confidence: 59%
“…Measurement of PON1 activity is an accepted indicator of the HDL antioxidant property and a promising biomarker of HDL function independently of HDL-C levels [20] . PON1 inhibits lipoprotein oxidation and macrophage foam cell formation.…”
Section: Discussionmentioning
confidence: 99%